2018
DOI: 10.1016/j.aju.2017.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Repair of panurethral stricture: Proximal ventral and distal dorsal onlay technique of buccal mucosal graft urethroplasty

Abstract: ObjectiveTo report the surgical details and results of our technique of buccal mucosal graft (BMG) urethroplasty for panurethral stricture, as many studies have reported repair of panurethral stricture by single-stage BMG urethroplasty by placing buccal mucosa ventrally, dorsally or dorsolaterally.Patients and methodsThis was an observational analysis of 38 patients with panurethral stricture treated by placing two BMGs, one as a ventral onlay in the proximal bulbar urethra and the other as a dorsal onlay in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Chodisetti et al also used combination ventral and dorsal grafts in LS patients, but exclusively used the ventral graft in the bulbar urethra where the ventral spongiosum is more robust than in the penile urethra. 20 The authors reported a 19% recurrence rate among patients with LS using this technique. Lastly, Kunz et al 25 and Al-Hakeem et al 14 describe performing mostly ventral graft urethroplasties; however, it is not clear if this technique was utilized for their subset of patients with LS as well.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Chodisetti et al also used combination ventral and dorsal grafts in LS patients, but exclusively used the ventral graft in the bulbar urethra where the ventral spongiosum is more robust than in the penile urethra. 20 The authors reported a 19% recurrence rate among patients with LS using this technique. Lastly, Kunz et al 25 and Al-Hakeem et al 14 describe performing mostly ventral graft urethroplasties; however, it is not clear if this technique was utilized for their subset of patients with LS as well.…”
Section: Discussionmentioning
confidence: 91%
“…A total of 21 studies were identified for inclusion in the review. 5,6,14–32 Figure 1 shows a detailed PRISMA flowchart of the selection process.…”
Section: Resultsmentioning
confidence: 99%